Utilization of Spotify Podcasts Based on the RICOSRE Model to Improve Students' Final Report Writing Skills - Sigit Widiyarto (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2026)
This study examines the effectiveness of using Spotify podcasts based on the RICOSRE model to improve students’ final report writing skills through a one-group pretest–posttest experimental design involving 89 students. The learning framework followed the RICOSRE stages (Reading, Identifying, Constructing, Solving, Reviewing, Extending) and used the podcast episode “Is AI Making Us Stupid” as authentic input. Data were collected  pre- and post-writing tests, documentation of instructional implementation, and student feedback; analyses included assumption testing, reliability and normality checks, and inferential tests (paired t-test and ANOVA) conducted with SPSS 23. The paired test showed a significant difference between scores before and after the intervention (mean difference ≈ -19.84; t = -19.624; p < .01), with a 95% confidence interval that did not cross zero, indicating a consistent change after the intervention. However, between-group ANOVA did not reach significance (F = 1.872; p = .065), indicating variation in effects across participant subgroups. Findings suggest  podcast-based instruction structured by RICOSRE can effectively improve overall writing ability, but subgroup-specific effectiveness requires further investigation. Methodologically, integrating authentic audio input with staged cognitive scaffolding offers a replicable intervention framework. Practical recommendations include integrating rubrics and regular feedback, training students to use podcasts as data sources.